THE UTILIZATION OF SHORT STORIES IN TEACHING AND LEARNING - Xojaniyazova Bazargul Mamabetovna (Journals Park Publishing, 2024)
Learning and utilizing words is the first step in learning a second language. Learners can improve their communication and ultimately acquire both productive and receptive language abilities when they are proficient in using the fundamental or everyday vocabulary of the target language. Given this understanding, English teachers began utilizing literary works to help students meet learning objectives and increase their vocabulary. In this sense, using short stories as a teaching and learning tool for vocabulary is a successful tactic that serves the needs of both teachers and students. This study is descriptive delving into the utilization of short stories in teaching and learning vocabulary. The vocabulary and usage of the terms that language learners know define their proficiency level.
Keywords: learning, communication, productive, receptive, proficient, fundamental, tactic.